Applied sonoanatomy of the posterior triangle of the neck - Ihnatsenka, Barys (Medknow Publications, 2010)
The posterior triangle of the neck is an area of the body frequently visited by regional anesthesiologists, acute and chronic pain physicians, surgeons of all disciplines, and diagnosticians. It houses the entire brachial plexus from the roots to the divisions, the scalene muscles, the cervical sympathetic ganglions, the major blood vessels to and from the brain, the neuroforamina and various other structures of more or less importance to these physicians. Ultrasound (US) offers a handy visual tool for these structures to be viewed in real time and, therefore, its popularity and the need to understand it. We will discuss pertinent clinical anatomy of the neck and offer a basic visual explanation of the often-difficult two-dimensional (2-D) images seen with US.